Association of Allergic Symptoms in the First 2 Years of Life With Sleep Outcomes Among Chinese Toddlers - Chen, Yujing; Lin, Lizi; Hong, Bin; Karatela, Shamshad; Pan, Wenting; Wu, Shengchi; Tang, Nu; Wang, Yuxuan; Jing, Jin; Cai, Li (Frontiers in Pediatrics, 2022)
Background: Previous studies have linked allergic symptoms to sleep in children, but the associations might be different when considering different types of allergic symptoms or sleep outcomes. Moreover, the combined effects of multiple allergic symptoms remain unclear in early life. This study aimed to investigate the associations between multiple allergic symptoms and sleep outcomes in early life. Methods: We included 673 toddlers aged 2 years from a birth cohort in Guangzhou, China. We identified allergic symptoms (skin, eyes and nose, gastrointestinal tract, mouth and lips, and wheeze) within 2 years via standard questionnaires. Sleep outcomes including sleep duration and quality over the past month were assessed based on the Chinese version of the Brief Infant Sleep Questionnaire. Associations between allergic symptoms and sleep outcomes were examined using multivariable linear regression and logistic regression. Results: Compared to children without allergic symptoms, children with allergic nasal and ocular symptoms had higher odds of frequent nighttime awakenings (OR=1.41; 95%CI: 1.03, 1.93) and irregular sleep (OR=1.45, 95%CI: 1.05, 2.00); children with allergic gastrointestinal symptoms slept 0.28 hours less during nighttime (95%CI: -0.48, -0.07) and 0.25 hours less per day (95%CI: -0.43, -0.08), and had 59% higher odds of irregular sleep (95%CI: 1.24, 2.04). We also found significant association of multiple allergic symptoms with shortened nighttime sleep duration and increased irregular sleep. Whereas, allergic skin, mouth and lips, and wheeze symptoms were not significantly associated with sleep outcomes. Conclusion: Allergic symptoms within 2 years of age were adversely associated with sleep outcomes, which highlight the importance of early screening of allergic symptoms in toddlers in order to improve their sleep outcomes.